What Happened to Patients With Obsessive Compulsive Disorder During the COVID-19 Pandemic? A Multicentre Report From Tertiary Clinics in Northern Italy - Benatti, Beatrice; Albert, Umberto; Maina, Giuseppe; Fiorillo, Andrea; Celebre, Laura; Girone, Nicolaja; Fineberg, Naomi; Bramante, Stefano; Rigardetto, Sylvia; Dell’Osso, Bernardo (Frontiers in Psychiatry, 2020)
After the outbreak of Coronavirus disease was declared a pandemic by the World Health Organization, this resulted in extraordinary public health measures to control the infection, such as entire countries being placed under quarantine. The psychopathological consequences of the pandemic and quarantine were anticipated to be of particular relevance, especially in patients with psychiatric disorders such as Obsessive Compulsive Disorder (OCD). Aim of the present report was to describe the impact of COVID-19 pandemics within a sample of Italian patients affected by OCD. Sociodemographic and clinical variables of a sample of 123 OCD outpatients, currently attending three OCD tertiary clinics in Northern Italy, were assessed through telephone and in-person interviews. Patients showing a clinical worsening of OCD represented more than one third of the sample and reported a significant increase of new obsessions and compulsions phenotypes along with a significant exacerbation of past ones. Moreover, they were more frequently found to experience suicidal ideation, increased Internet checking, sleep disturbances, avoidance behaviors and work difficulties. A significantly increased need of therapy adjustment and family accommodation was also observed. Further research is warranted to clarify the potential risk and related consequences of the current COVID-19 pandemic on OCD patients.